ANALISIS PENGARUH INVESTASI,PENDAPATAN ASLI DAERAH,DAN JUMLAH PENDUDUK DALAM MENSTIMULASI PERTUMBUHAN EKONOMI DI KALIMANTAN BARAT - B01109028, ARDISKA ABZENI TIA (Jurnal Curvanomic, 2016)
This study was conducted to analyze investment, revenue and the number of people effect that stimulating economic growth in West Kalimantan Year 2000-2011. The purpose of this study to determine investment, revenue and population affect the economic growth in West Kalimantan. An author in this research uses secondary data, time series data and start from 2000-2011 were obtained from the BPS West Kalimantan Province. Then the data is analyzed using quantitative analysis. Quantitative analysis includes multiple regression, the coefficient of determination test, F-test, t-test, multicollinearity, autocorrelation, heteroscedasticity test Based on the results obtained Â² test and F-test test has a strong influence on economic growth. Partial or tcount test, investment and population has a positive and significant effect on economic growth, while the PAD has a positive influence and not significant. In multicollinearity test, the variable investment and revenue does not happen multicollinearity occurs while the population of multicollinearity. In the autocorrelation test, the model used an element of positive autocorrelation or have distract element. In heterocedastisity test is known that there is no problem because the heterocedastisity critical value (X2) is greater than chi square value.